Autonomous capillary electrophoresis processing and analysis of dried blood spots for high-throughput determination of uric acid - Moravčík, Ondrej; Dvořák, Miloš; Kubáň, Pavel (Analytica chimica acta, 2023)
A new set-up for fully autonomous and high-throughput capillary electrophoresis (CE) analyses of dried blood spot (DBS) samples is presented. The DBS samples were prepared by collecting exactly 5 μL of capillary blood from a finger-prick onto a pre-punched DBS disc in a disposable plastic CE vial and by in-vial blood drying. The vials with the DBS samples were then loaded into a commercial CE instrument for a fully unmanned sample processing and analysis. A fused-silica capillary of the CE instrument was first used for the transfer of 100 μL of elution solvent to each vial, in-vial DBS elution, and in-vial eluate homogenization. The same capillary was also used for at-line injection, separation, and selective analysis of the resulting eluates. Novel CE sequences were tailor-programmed for consecutive processing and analyses of multiple DBSs, which facilitated a fully autonomous determination of uric acid with a throughput of 240 DBS samples per day (24 h). The presented analytical protocol (using 100 μm i. d./30 cm capillary; 30 mM 2-(N-morpholino)-ethanesulfonic acid, 30 mM l-histidine, and 30 μM cetyltrimethylammonium bromide background electrolyte solution; and UV detection at 292 nm) provided excellent precision at endogenous and spiked uric acid concentrations with RSD values of peak areas below 3.2%. Calibration curves were linear over the 33.3 − 1200 μM range (R2 better than 0.998), limits of detection and quantification in the original capillary blood were 10 and 33.3 μM, respectively, and were well below the uric acid clinical range (140–420 μM). The stability of uric acid in DBS samples stored at laboratory temperature for up to 2 months was also excellent demonstrating less than a 4.2% decrease in uric acid concentrations. The actual set-up might thus be highly attractive for clinical subjects and laboratories because it is minimally invasive and requires minimum intervention from laboratory staff. [Display omitted] •High-throughput dried blood spot (DBS) analyses by commercial capillary electrophoresis.•Autonomous elution, processing, and analysis of multiple DBSs by a single instrument.•Rapid in-vial DBS pretreatment and selective at-line analyses of the resulting DBS eluates.•Analyses of up to 240 DBSs per day for the determination of uric acid as a clinical marker.•Suitable also for remote blood microsampling and transport to a lab for unmanned analyses.